1991
DOI: 10.12693/aphyspola.79.531
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Orbit-Lattice Interactions for PbF2:Gd3+Single Crystals

Abstract: Temperature dependence of the second-order spin-lattice coefficients for PbF2:Gd3+ is reported. It is shown that the thermal expansion of the crystal 1attice contributes only in about 14 % to the observed dependence and the rest should be ascribed to a dynamic coupling between the 4f 7 electrons and lattice vibrations. The results are parametrized in both the Einstein and the Debye models and it is shown that the phenomenological parameters obtained from such parametrization can be made to coincide in both mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1992
1992
2002
2002

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…On the other ha nd, i n G d 3 + -do p ed PbF 2 sing l e crysta l the val ue of K 2 = À 0 : 1 0 7 9 G Hz for tetra gona l deform ati ons and K 2 = 0 : 3 6 8 8 G Hz for tri gona l deform ati ons wa s obta i ned f rom EPR uni axi al stress exp eri ment i n the tem pera ture ra nge 130{ 600 K by Kuri ata et al . [29 ]. Thi s shows tha t di sto rti on of the crysta l Ùel d (tri gona l i s l ower sym m etry tha n tetra gona l ) i nÛuences signi Ùcantl y the 4 f 7 electro n{ pho no n coupl i ng consta nt K 2 .…”
Section: R Esu L T S An D Discussionmentioning
confidence: 95%
“…On the other ha nd, i n G d 3 + -do p ed PbF 2 sing l e crysta l the val ue of K 2 = À 0 : 1 0 7 9 G Hz for tetra gona l deform ati ons and K 2 = 0 : 3 6 8 8 G Hz for tri gona l deform ati ons wa s obta i ned f rom EPR uni axi al stress exp eri ment i n the tem pera ture ra nge 130{ 600 K by Kuri ata et al . [29 ]. Thi s shows tha t di sto rti on of the crysta l Ùel d (tri gona l i s l ower sym m etry tha n tetra gona l ) i nÛuences signi Ùcantl y the 4 f 7 electro n{ pho no n coupl i ng consta nt K 2 .…”
Section: R Esu L T S An D Discussionmentioning
confidence: 95%
“…The experimental data reported in [1] indicated that the temperature dependence of the second-order spin-lattice coefficients for PbF2:Gd 3+ can be parametrized in the Einstein as well' as the Debye models if the "averaged" frequency for the optical modes is chosen to be ωE = 2.5 x 10 13 8-1 . The Einstein model will be analyzed below due to its simplicity.…”
Section: The Results and Comparison With Experimental Datamentioning
confidence: 99%
“…The Einstein model will be analyzed below due to its simplicity. In this model the temperature dependence of the second-order spin-lattice parameters is parametrized by the following function (see for example [1]):…”
Section: The Results and Comparison With Experimental Datamentioning
confidence: 99%
See 2 more Smart Citations